Effect of Conventional Agriculture Financing on Development of Small-Scale Farming in Nigeria - Jatto , Yusuf; Gambo, Sanusi (Kashere Journal of Politics and International Relations, 2025)
This study explores the impact of conventional agriculture financing on the development of small-scale farming in Nigeria. Conventional financing, primarily through commercial banks, microfinance institutions, and government-backed credit schemes, plays a critical role in supporting agricultural productivity. However, small-scale farmers often face barriers such as limited access to credit, high interest rates, and stringent collateral requirements, which undermine their ability to fully benefit from these financial services. The overview highlights how these challenges affect farm output, technology adoption, and overall livelihood improvement among smallholder farmers. Additionally, it examines the effectiveness of existing financing models and policies in bridging the funding gap. By synthesizing recent studies, policy reports, and field data, the paper identifies gaps in current financing structures and proposes strategies for more inclusive and sustainable financial interventions. Ultimately, the study underscores the need for a more flexible, accessible, and farmer-friendly financing framework to enhance the productivity and resilience of small-scale agriculture in Nigeria.